2017
DOI: 10.1186/s13063-017-2213-z
|View full text |Cite
|
Sign up to set email alerts
|

The added value of a mobile application of Community Case Management on referral, re-consultation and hospitalization rates of children aged under 5 years in two districts in Northern Malawi: study protocol for a pragmatic, stepped-wedge cluster-randomized controlled trial

Abstract: BackgroundThere is evidence to suggest that frontline community health workers in Malawi are under-referring children to higher-level facilities. Integrating a digitized version of paper-based methods of Community Case Management (CCM) could strengthen delivery, increasing urgent referral rates and preventing unnecessary re-consultations and hospital admissions. This trial aims to evaluate the added value of the Supporting LIFE electronic Community Case Management Application (SL eCCM App) compared to paper-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
(38 reference statements)
0
32
0
Order By: Relevance
“…The trial was conducted from October 2016 to February 2017 in Rumphi and Nkhata Bay districts, Northern Malawi (methods described in full elsewhere) [17]. Qualitative interviews were conducted with participants between January–February 2017 at village clinics, participants’ homes, or a community facility convenient to participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was conducted from October 2016 to February 2017 in Rumphi and Nkhata Bay districts, Northern Malawi (methods described in full elsewhere) [17]. Qualitative interviews were conducted with participants between January–February 2017 at village clinics, participants’ homes, or a community facility convenient to participants.…”
Section: Methodsmentioning
confidence: 99%
“…However, the impact of interventions on CHWs’ referral patterns and caregivers’ subsequent health-seeking behavior, to our knowledge, has yet to be investigated. We sought to address this in a clinical trial [17]. We investigated the acceptability of delivering CCM via an mHealth solution among CHWs, known in Malawi as Health Surveillance Assistants (HSAs), and parents/caregivers (referred to as caregivers hereafter), with a particular emphasis on factors that might influence its impact on referrals from community clinics to higher-level health care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…8 Implementation of these digital protocols on smartphones or tablets by FLW has shown the potential to increase the number of children being checked for important clinical danger signs, improved antibiotic use, and referrals for consultations and hospitalizations. 5,9,10 A clinician-based study in Tanzania demonstrated that digitalized modified IMCI-ALMANACH algorithms in conjunction with selective point-of-care tests achieved a reduction of 43% in the proportion of clinical failures, a 58% reduction in the proportion of severe adverse events, and a substantial decrease in the proportion of antibiotic prescriptions from 30% to 11% compared with the traditional IMCI-ALMANACH algorithms. 11 Despite these important improvements, current IMCI-iCCM–based and other mHealth platforms have not demonstrated consistency with implementation or a high agreement with expert clinical assessments of children with important clinical conditions such as pneumonia (26–41%).…”
Section: Introductionmentioning
confidence: 99%
“…Several programs of work (in Malawi 19 and Uganda 20 ) have either adopted double assessment and data entry approaches, or have utilized mobile iCCM to direct assessment and data entry into patient records. Whilst it is impossible to speculate on why these procedures were selected in these instances (interoperability may or may not have been the rate limiting step), the authors can identify that lack of interoperability was a crucial determinant of the decision to investigate the added value of a mobile version of iCCM in a feasibility study and clinical trial, as part of the Supporting LIFE program 21 . Whilst adding or integrating mobile iCCM with paper iCCM generates some insight into the potential benefits, we have limited understanding of relationships between mobile versions of iCCM and most clinical, process, patient-reported and cost-related outcome measures.…”
Section: Interoperability As the Final Connectionmentioning
confidence: 99%